2018
DOI: 10.1080/03008207.2018.1483361
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological, immunohistochemical, and biomechanical effects of splenectomy on Achilles tendon healing in rats

Abstract: Splenectomy may positively influence Achilles tendon healing through modification of the proinflammatory/anti-inflammatory ratio in favor of anti-inflammatory cytokines by causing a decrease in spleen-originated inflammatory cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…Proper inflammatory responses are likely to be necessary for tissue regeneration, which may be impaired by the high levels of proinflammatory cytokines . Yuksel et al reported that reduced proinflammatory cytokines (such as IL-1β, TNF-α) and unregulated anti-inflammatory cytokines (such as IL-2, IL-10) positively influenced Achilles tendon healing . We also found that the secretions of IL-2, IL-4, IL-10, and IL-17 significantly increased in the TEDA group compared with the DA group from months 1 to 3, which is an important period of ACL ligament remodeling and tendon–bone healing.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Proper inflammatory responses are likely to be necessary for tissue regeneration, which may be impaired by the high levels of proinflammatory cytokines . Yuksel et al reported that reduced proinflammatory cytokines (such as IL-1β, TNF-α) and unregulated anti-inflammatory cytokines (such as IL-2, IL-10) positively influenced Achilles tendon healing . We also found that the secretions of IL-2, IL-4, IL-10, and IL-17 significantly increased in the TEDA group compared with the DA group from months 1 to 3, which is an important period of ACL ligament remodeling and tendon–bone healing.…”
Section: Discussionsupporting
confidence: 65%
“…48 Yuksel et al reported that reduced proinflammatory cytokines (such as IL-1β, TNF-α) and unregulated anti-inflammatory cytokines (such as IL-2, IL-10) positively influenced Achilles tendon healing. 49 We also found that the secretions of IL-2, IL-4, IL-10, and IL-17 significantly increased in the TEDA group compared with the DA group from months 1 to 3, which is an important period of ACL ligament remodeling and tendon− bone healing. IL-17-treated tenocytes were reported to increase the expression of collagen III.…”
Section: ■ Discussionsupporting
confidence: 51%
“…However, the levels of circulating CD4+ and CD8+ T lymphocytes and their alterations should be detected in SCD patients with COVID‐19 to confirm the above hypothesis. (2) Benefit of splenectomy in animal models, with decreased proinflammatory/anti‐inflammatory ratio through a decrease in spleen‐originated inflammatory cells 51 . Since only four SCD patients with splenectomy and good outcomes were reported, 7,11,15,30 the possible benefit of splenectomy against the produced cytokine storm in COVID‐19 patients needs to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory effect and inflammatory cytokine reduction have been reported in an animal study after splenectomy. However, the beneficial role of splenectomy against cytokine storms and severe forms of COVID-19 in patients with β-thalassemia needs to be confirmed (37).…”
Section: Splenectomy and Iron Overloadmentioning
confidence: 99%